Measuring alluvial fan sensitivity to past climate changes using a self-similarity approach to grain size fining, Death Valley, California - D'Arcy,M; Whittaker,AC; Roda,Boluda DC (Sedimentology, 2016)
The effects of climate change on eroding landscapes and the terrestrial sedimentary record are poorly understood. Using mountain catchment–alluvial fan systems as simple analogues for larger landscapes, a wide range of theoretical studies, numerical models and physical experiments have hypothesised that a change in precipitation rate could leave a characteristic signal in alluvial fan sediment flux, grain size and down-system fining rate. However, this hypothesis remains largely untested in real landscapes. This study measures grain-size fining rates from apex to toe on two alluvial fan systems in northern Death Valley, California, USA, which each have well-exposed modern and ca 70 ka surfaces, and where the long-term tectonic boundary conditions can be constrained. Between them, these surfaces capture a well-constrained temporal gradient in climate. A grain-size fining model is adapted, based on self-similarity and selective deposition, for application to these alluvial fans. This model is then integrated with cosmogenic nuclide constraints on catchment erosion rates, and observed grain-size fining data from two catchment-fan systems, to estimate the change in sediment flux from canyon to alluvial fan that occurred between mid-glacial and modern interglacial conditions. In a fan system with negligible sediment recycling, an approximately 30% decrease in precipitation rate led to a 20% decrease in sediment flux and a clear increase in the down-fan rate of fining, supporting existing landscape evolution models. Consequently, this study shows that small mountain catchments and their alluvial fan stratigraphy can be highly sensitive to orbital climate changes over <105 year timescales. However, in the second fan system it is observed that this sensitivity is completely lost when sediment is remobilised and recycled over a time period longer than the duration of the climatic perturbation. These analyses offer a new approach to quantitatively reconstructing the